AB1012 Bone mass changes correlate with disease activity in non-arthropathic psoriatic patients. (12th June 2018) - Paolino, S.; Gotelli, E.; Pacini, G.; Alessandri, E.; Casabella, A.; Ghio, M.; Cattelan, F.; Goegan, F.; Patané, M.; Cutolo, M.
Abstract : Background: Psoriasis is a chronic inflammatory skin disease, and as all inflammatory processes, it could induce osteoclast activation 1 ending up with osteoporosis. It is well known that a recognised contributing factor to bone strength, independent from bone mass, is micro-architectural damage; therefore, evaluation of microarchitecture seems to be necessary to get adequate information about bone quality health. Trabecular bone score (TBS) is a new tool to assess bone quality. 2 To date, studies on TBS assessment in psoriasis are lacking, even if it was suggested to be correlated with inflammation and metabolic parameters. 3 Objectives: The aim of the study was to investigate bone quality and bone quantity in psoriatic patients without arthropathic involvement and its relationship with dermal disease activity (PASI). Methods: Thirty-five psoriatic patients and thirty-four healthy controls were enrolled. We first assessed Body Mass Index (BMI), Bone Mineral Density (BMD) and Trabecular Bone Score (TBS) in both patients and healthy control. The Bone Mineral Density (BMD) (g/cm2) was analysed by dual-energy X-ray absorptiometry scan (Lunar Prodigy) and, using same machine, anteroposterior spine analysis was performed to evaluate TBS for L1-L4 using TBS insight Medimaps software. TBS >1.350 units was considered normal. Psoriatic patients were also divided in two subgroups according to skin lesion presentation (plaque psoriasis and guttate psoriasis) and dermal disease activity was measured by Psoriasis Area and Severity Index (PASI). Results: In the psoriatic cohort (mean age 62.8±12.6 years, BMI 27.8±3.4 g/m 2, disease duration 18.6±11.9 years, PASI 8.3±7.6) 36% of patients showed low bone mass, particularly, 33.3% showed osteopenia and 2.7% osteoporosis. There was not significantly statistical difference between mean BMD and TBS in psoriatic patients when compared to the healthy control group. However, in psoriatic patients a negative correlation between neck-BMD and PASI (p=0.003) was detected independently of sex and age. Conversely, TBS was not statistically correlated with PASI or with BMI. It was interesting to verify that the plaque psoriasis group showed a positive correlation between PASI and age (p=0.01). Conversely, PASI was negatively correlated with lumbar spine T-score (p=0.01) and both lumbar spine and femoral neck BMD (p=0.04 and p=0.02 respectively). Conclusions: This pilot study suggests that in psoriasis, particularly in the plaque subgroup, the severity of skin involvement might correlate with bone mass but not with bone quality (TBS). Despite previous evidences, we can't assess any correlation between TBS and metabolic parameters. Furthers studies with larger cohorts are needed on this topic. References: [1] Attia EA, et al., J Dermatol2011; 50:30–35. [2] Silva Bc, et al., J Bone Miner Res2014;29:518–30. [3] Hernandéz JL, et al., J Osteoporosis, 2016; 5747852 Disclosure of Interest: None declared